Erratum: SCHORIES, S., MEYER, M.K. & SCHARTL, M. (2009) Description of Poecilia (Acanthophacelus) obscura n. sp., (Teleostei: Poeciliidae), a new guppy species from western Trinidad, with remarks on P. wingei and the status of the “Endler’s guppy”. Zootaxa, 2266, 35–50. - Schories, S.; Meyer, M. K.; Schartl, M. (Zootaxa, 2009)
(Erratum)